Elliptical cylinder metallic array for enhancing room-temperature midwave infrared photodetection - Tong, Jinchao (2021)
Metasurface, from periodical and artificial structures of 'meta-atoms' constructed by subwavelength-sized metallic resonators, has been incorporated with optoelectronic devices to realize improved and multifunctional performance. Here, we report a fourfold rotationally-symmetric elliptical cylinder metasurface for enhancing photodetection in the midwave infrared (2–5 µm) range. This metasurface has the capability to confine light within a small volume and has polarization-independence property. An enhanced photodetector consisting of this metasurface and an InAsSb-based heterojunction photodiode is fabricated and evaluated in detail. Polarization-independent improvement for performance is achieved. A fourfold specific detectivity (D*) improvement (to 3.3  ×  109 Jones) compared to that of a reference photodiode is achieved for room-temperature operation. Electrically controlled enhancement for the enhanced device is observed with a maximum enhancement factor of six (600%) for photocurrent (or responsivity). The enhanced photodiode has response speed similar to that of the reference.